A High‐Energy NASICON‐Type Cathode Material for Na‐Ion Batteries. Issue 10 (3rd February 2020) - Wang, Jingyang; Wang, Yan; Seo, Dong‐Hwa; Shi, Tan; Chen, Shouping; Tian, Yaosen; Kim, Haegyeom; Ceder, Gerbrand
Abstract: Over the last decade, Na‐ion batteries have been extensively studied as low‐cost alternatives to Li‐ion batteries for large‐scale grid storage applications; however, the development of high‐energy positive electrodes remains a major challenge. Materials with a polyanionic framework, such as Na superionic conductor (NASICON)‐structured cathodes with formula Na x M2 (PO4 )3, have attracted considerable attention because of their stable 3D crystal structure and high operating potential. Herein, a novel NASICON‐type compound, Na4 MnCr(PO4 )3, is reported as a promising cathode material for Na‐ion batteries that deliver a high specific capacity of 130 mAh g −1 during discharge utilizing high‐voltage Mn 2+/3+ (3.5 V), Mn 3+/4+ (4.0 V), and Cr 3+/4+ (4.35 V) transition metal redox. In addition, Na4 MnCr(PO4 )3 exhibits a high rate capability (97 mAh g −1 at 5 C ) and excellent all‐temperature performance. In situ X‐ray diffraction and synchrotron X‐ray diffraction analyses reveal reversible structural evolution for both charge and discharge. Abstract : A new Na superionic conductor (NASICON)‐type Na4 MnCr(PO4 )3 is synthesized and evaluated as a cathode material for Na‐ion batteries. It delivers 130 mAh g −1 discharge capacity utilizing Mn 2+/4+ and Cr 3+/4+ redox. Unlike known NASICONs, one more Na extraction is achieved at the high‐voltage end. X‐ray absorption and diffraction studies are performed to reveal the redox mechanism and structural evolution in detail.